Gender-specific therapeutic approach in arterial hypertension – Challenges ahead. (March 2019) - Tadic, Marijana; Cuspidi, Cesare; Grassi, Guido; Ivanovic, Branislava
Graphical abstract: Abstract: Hypertension was thought to be more important cardiovascular risk factor in men than in women. However, studies showed that overall incidence of hypertension-related cardiovascular diseases is higher in women comparing with men and this is particularly valid in menopause when prevalence of hypertension and its complications sharply and suddenly rises. It was also noticed that the effect of various antihypertensive groups was different in women and men. Some medications are prescribed more often in women, but it does not necessary mean that these drugs are more effective in this gender. There are several important reasons that could explain gender-induced differences in blood pressure levels, blood pressure control and antihypertensive treatment. They involve sex hormones, the renin-angiotensin-aldosterone and sympathetic nervous system, and arterial stiffness. However, taking into account many observational studies and trials, there are no consistent data regarding the impact of gender on effect of antihypertensive medications. Longitudinal study focused on gender and current antihypertensive groups would significantly help to understand the impact of gender. This might change therapeutic approach and improve cost-effectiveness in antihypertensive therapy in both genders. A full understanding of the pathophysiological characteristics of variations between genders demands additional research. This review article summarized the current knowledge regarding differences in the prevalence and awareness of arterial hypertension in women and men; alterations in pathophysiological mechanisms of hypertension between sexes; as well as the impact of sex on the effects of main antihypertensive groups of medications.